Menara Tabung Haji Platinum, KLCC Kuala Lumpur / Hamzah Faris Hilmi Habri ... [et al.] - Hamzah Faris Hilmi, Habri; Nurul Ain Aisyah, Zulkifli; Amni Amalia, Mahadzir; Nazim, Bahaman; Abang Abdul Hadi, Rabaiee (2019)
This report is about Menara Tabung Haji Platinum building which located at the Platinum Park, KLCC. This report is about the building and the maintenance system that was used in the building. In this report, all the information that has been collated during site visit at the Menara Tabung Haji Platinum and interviewing some person in charge for our final project. Mostly, the services used in Menara Tabung Haji is similar to other normal office building. But the special things about Menara Tabung Haji Platinum is this building got the certified as green building. This building was using their own maintenance management which is TH Universal Builders. They were function to run the maintenance inside the building plus with outsource maintenance. Overall, the maintenance work in Menara Tabung Haji Platinum still in good maintenance as it is a new building. But their still need to improve in their planning for maintenance.